Psychometric Properties of the GAD-7 for Assessing Anxiety Disorder Among Students and Populations in Developing Countries: A Systematic Review - Haris Petriano; Retno Lestari; Heni Dwi Windarwati (Journal An-Nafs: Kajian Penelitian Psikologi, 2025)
Generalized anxiety disorder (GAD) is one of the most common anxiety disorders and significantly impacts individual well-being. Early detection using a valid instrument, such as the GAD-7, is essential for effective intervention. However, evidence regarding the psychometric performance of the GAD-7 in developing countries remains fragmented, particularly across student and community populations, necessitating systematic synthesis. This study aimed to systematically review and synthesise evidence on the psychometric properties of the GAD-7, including its validity, reliability, cut-off values, and cultural adaptability, among students and general populations in developing-country contexts. A systematic review was conducted using three databases: PubMed, ScienceDirect, and SAGE Journals. The search employed the keywords “Anxiety Disorder,” “Developing Country,” “Generalized Anxiety Disorder-7,” “Mental Health,” “Psychometric,” and “Student,” using Boolean operators (AND, OR). Of the 3,255 records identified, 15 studies met the inclusion criteria after screening and eligibility assessment and were included in the final synthesis. The review demonstrates that the GAD-7 shows consistently strong construct validity, a stable unidimensional factor structure, and robust convergent validity across diverse cultural and educational settings, with positive correlations observed with related instruments such as the PHQ-9. With high internal consistency (Cronbach’s α = 0.85–0.93) and a commonly supported cut-off score of ≥10, the GAD-7 effectively identifies anxiety symptoms, although context-specific lower cut-off scores were reported in certain clinical and community populations. Overall, the findings indicate that the GAD-7 is a valid, reliable, and culturally adaptable screening instrument for anxiety assessment. By consolidating psychometric evidence across developing-country contexts, this review provides an integrated and up-to-date synthesis that supports the informed use of the GAD-7 in educational, clinical, and public mental health settings, particularly in low-resource environments.